Pengaruh Penggunaan Alat Permainan Edukatif Terhadap Kemampuan Kognitif Anak Usia 4–5 Tahun Di Paud Lobi-Lobi Jakarta - Dian Mariati; Desy Ayuningrum (Universitas Islam Negeri Jurai Siwo Lampung, 2025)
This study aims to investigate the impact of educational games (APE) on the cognitive development of children aged 4–5 years. The research method used was an experiment with a pre-test–post-test control group design. The research sample consisted of 20 children divided into two groups. The experimental group (10 children) used APE, while the control group (10 children) followed conventional learning. The research instrument was a cognitive development observation sheet. It covered recognizing shapes, colors, numbers, simple logical thinking, and problem-solving. The results showed a significant difference between the experimental and control groups. The average pre-test score of the experimental group was 2.40, which increased to 4.10 in the post-test. This was an average increase of 1.70 points. The control group only increased from 2.35 to 2.90, with an average increase of 0.55 points. The t-test results showed a p-value of 0.0004 (<0.05), indicating that the research hypothesis was accepted. Thus, it can be concluded that play-based educational materials (APE) have a positive and significant impact on the cognitive abilities of children aged 4–5 years. APE has been proven effective in stimulating children's cognitive development. It provides concrete, enjoyable, and developmentally appropriate experiences. The results of this study can serve as a reference for teachers, parents, and early childhood education institutions. These findings may help improve the quality of play-based learning.